An overview of extension use in irrigated agriculture and case studies in south-eastern Africa. Issue 5 (3rd September 2017) - Wheeler, Sarah Ann; Zuo, Alec; Bjornlund, Henning; Mdemu, Makarius Victor; van Rooyen, Andre; Munguambe, Paiva
Abstract: This study provides an overview of extension influence on the adoption of irrigation innovations in developed and developing countries, and finds that extension plays a more significant positive role in influencing soft technology adoption in developing countries. Case studies on the nature, use and availability of extension advice in six irrigation schemes in Tanzania, Mozambique and Zimbabwe are presented. The use of government extension officers varied significantly, with extension use not linked to farm outcomes. The results suggest the need to support more diverse sources of advice and to promote institutional reform in south-eastern Africa.